ASSESSING WORTHINESS IN BOOK REVIEW ARTICLES: AUTHORS’ STRATEGIES IN EVALUATING THE REVIEWED BOOKS - Mardi Juansyah; Safnil Arsyad; Zifirdaus Adnan (PAROLE: Journal of Linguistics and Education, 2025)
Book review articles highlight the worthiness of new publications through critical insights, encouraging deeper interest and appreciation among readers. Previous studies often lack focus on journal reputation and publication regions. This study aims to analyse authors’ common rhetorical pattern and strategies for evaluating and issuing final opinions. Forty-eight articles from eight Scopus-indexed journals in language-related field were analysed using four moves with sixteen steps model. The results indicate that the first three moves (Introducing the book, Summarizing the content, and Evaluating the book) are obligatory, while Issuing a final opinion is conventional. Additionally, two steps (Defining the general topic of the book and Providing a general assessment) consistently appear. The analysis reveals that the authors tend to use praise more frequently than criticism in their evaluations, particularly when assessing the book as a whole. Furthermore, the findings show that authors primarily provide recommendations and rarely disqualify the works for final judgment. This study has important implications for novice writers, as they should be familiar with the rhetorical structure and aware of the strategies used for evaluating and issuing final opinions in book review articles, thereby enhancing their chances of publication in high-impact journals.